2014
DOI: 10.33073/pjm-2014-043
|View full text |Cite
|
Sign up to set email alerts
|

Laccase Production by Trameteshirsuta, Characterization, and Its Capability of Decoloring Chlorophyll

Abstract: The present study focused on laccase production, characterization, and its involvement in chlorophyll decolorization. Extracellular laccase, with the highest activity of 11 U/ml on day 8, was efficiently produced from Trametes hirsuta in 5 l bioreactor with optimized media comprising dual carbon sources, glucose and water hyacinth. A laccase was then purified from the supernatant to homogeneity with purification fold of 9.51 and recovery of 39.8% and an estimated molecular mass of 62 kDa by SDS-PAGE. The lacca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Previous investigations have shown that T. hirsuta produces very active laccase ( 45 , 46 ), which was also noted in this research. However, the F13 did not show LiP activity.…”
Section: Resultssupporting
confidence: 88%
“…Previous investigations have shown that T. hirsuta produces very active laccase ( 45 , 46 ), which was also noted in this research. However, the F13 did not show LiP activity.…”
Section: Resultssupporting
confidence: 88%
“…The degradation efficiency, however, varies greatly depending on the single strains and species, as demonstrated in GC/MS tests. The causes may be different environmental growing conditions and substrate types, but especially adaptation to the presence of toxic agents such as pesticides, PAHs, and chlorinated agents [62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…Laccases are known for their ability to function optimally under neutral to slightly acidic conditions [32]. The increased activity at 60°C might be attributed to the enzyme's ability to maintain its stability and catalytic e ciency at elevated temperatures, although further investigations into its thermal stability are warranted [33].…”
Section: Ph and Temperature Optimamentioning
confidence: 99%